Confluence : The History of Fort Snelling - Smith, Hampton, 1949- (Book collections on Project MUSE., 2021)
"Fort Snelling, a foundational place in the story of Minnesota, was built two hundred years ago at the confluence of the Mississippi and Minnesota Rivers, an area known to the Dakota people as Bdote This book delves into the fort's long and complicated story: its construction, the daily lives of its inhabitants and those who lived nearby, the shift in its function when a spectacular influx of speculators and land-hungry immigrants flooded the territory, its participation in wresting the land from the Dakota, and its evolution as two cities grew up around it and its roles in two world wars-up to the reinterpretation of the fort as Minnesotans mark its two-hundredth anniversary"--